IMPLEMENTASI KEGIATAN OUTBOUND DALAM UPAYA PEMBENTUKAN PERILAKU SOSIAL DAN EMOSIONAL ANAK USIA DINI - Hermawati Dwi Susari (Universitas PGRI Madiun, 2011)
As social beings, egocentrism which is a character of preschoolers needs to be encouraged and guided in order not to hinder their future socialization in their community. In that perspective, this research aims to investigate how to use outbond activity as a means to build social-emotional behaviors of preschoolers. The results show that the social and emotional behaviors of the preschoolers at the kindergarten Sekolah Alam Bandung developed fairly well. Their emotion showed their ability to identify and understand the emotion they were experiencing but not able to control it. The plan and the application were already on the right track. However, there should be improvement. Problems encountered involved teacher’s restriction of knowledge, and the skill to serve as a preschool educator as well as the outbond facilitator. It was shown that the outbond activity affected less signifacntly their social and emotional behaviors. Accordingly, it is recommended the significance of enhancing teachers’ knowledge and skills in designing, applying and evaluating the outbond activity in order to better build preschoolers’ social and emotional behaviors.